1998
DOI: 10.1001/jama.280.6.550
|View full text |Cite
|
Sign up to set email alerts
|

Do We Know What Inappropriate Laboratory Utilization Is?

Abstract: Objective.-Laboratory utilization has steadily increased, and some studies suggest inappropriate utilization. Therefore, we wished to assess studies that measure inappropriate laboratory use in light of methodological criteria.Design.-Systematic review of published studies. Data Sources.-MEDLINE, HEALTHSTAR, and EMBASE databases were searched from 1966 to September 1997 using a broad and inclusive strategy with no language restriction. In addition, the references of all retrieved studies and 3 textbooks on dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
83
0
8

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(91 citation statements)
references
References 118 publications
0
83
0
8
Order By: Relevance
“…Gereksiz test istemleri, artan laboratuvar kullanı-mının en önemli nedenini oluşturmaktadır (11) (12) . Tüm bu nedenler test kullanımındaki artışa neden olsa da bu artıştaki en önemli pay gereksiz test istemlerince oluşturulmaktadır (11) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Gereksiz test istemleri, artan laboratuvar kullanı-mının en önemli nedenini oluşturmaktadır (11) (12) . Tüm bu nedenler test kullanımındaki artışa neden olsa da bu artıştaki en önemli pay gereksiz test istemlerince oluşturulmaktadır (11) .…”
Section: Discussionunclassified
“…Tüm bu nedenler test kullanımındaki artışa neden olsa da bu artıştaki en önemli pay gereksiz test istemlerince oluşturulmaktadır (11) . Hastanemiz Bilgi İşlem Biriminden retrospektif olarak elde ettiğimiz verilerden yaptığımız çalışma-da, sPSA test istemlerini inceledik.…”
Section: Discussionunclassified
“…This can hasten healing and improve the quality of life of the patient, while avoiding inappropriate costs to the national health system and patient [21]. Many studies have explored the potential to avoid unnecessary costs resulting from inappropriate therapy [22][23][24], but this is the first that focuses on mycotic skin infections and cost savings that…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of clinical laboratory audits found 5% to 50% of laboratory testing could be classified as inappropriate. 4 In the only published study of the appropriateness of a genetic test, 17% of APC tests for familial adenomatous polyposis were found to be requested for inappropriate indications. 5 The only previous report of DGT was included in a study of genetic testing in liver transplant patients where seven duplicate genetic tests were identified in a cohort of 215 patients.…”
Section: Discussionmentioning
confidence: 99%